ANALYSIS OF VELOCITY SLIP BETWEEN FLAT IN LUBRICATING FILM UNDER CONDITIONS OF THIN GAS - NING FangWei; LONG Wei; GONG Ling; PEI Hao; YANG ShaoHua (Jixie qiangdu)
When lubricating gas film of aerostatic guide way worked in micron level,internal airflow was affected by rarefied gas,the pressure and flow rate along flow direction was different to the result of calculating. In the gas film height direction,due to the characteristic scale decreased,the effect of gas molecule was intensified,traditional assumption of ignored vertical pressure gradient no longer founded,not only interior air film present obvious stratified trend,but velocity slip phenomenon was more significant. Simulating flow patterns and calculating its velocity and pressure in gas film by LAMMPS（ Large-scale Molecular Massively Parallel Simulator）,LBM（ Lattice Boltzmann Method） and Fluent in this paper,came to the relevant conclusion: the gas film in the longitudinal direction was divided into pressure-driven area and Newton friction area,and it also was divided into near wall layer,thin layer,continuous flow layer along its height direction,velocity slip mainly occurred in the near wall layer and thin layer of pressure-driven area. Gas stratification and velocity slip present in pressure-driven and Newton friction areas;Gas Stratification and velocity slip was enhanced with increasing gas flow rate,gas film stratification in Newton friction zone was gradually weakening,slippage speed gradually degenerated into near-wall boundary layer.